The influence of low-level sarin inhalation exposure on spatial memory in rats - Kassa, J; Koupilová, M; Vachek, J (Pharmacology, biochemistry, and behavior, 2001)
To study the influence of low-level sarin exposure on cognitive functions, the rats were exposed to three various low concentrations of sarin (Levels 1-3) for 60 min in the inhalation chamber. In addition, one group of rats was exposed to Level 2 of sarin repeatedly. Testing of cognitive functions was carried out using the Y-maze evaluating learning and spatial memory. The correct averse behavior of sarin-exposed rats in the Y-maze was tested several times within 6 weeks following sarin inhalation exposure to look for any cognitive impairments. The results were compared to the Y-maze performance of control rats exposed to pure air instead of sarin. While a subtle and short-term deficiency in the Y-maze performance was observed in rats exposed to the Levels 1 and 2 of sarin, the exposure to the Level 3 of sarin caused a significant decrease in the Y-maze performance for a relatively long time. Similar sarin-induced spatial memory impairments were demonstrated in rats exposed repeatedly to the Level 2. A decrease in the Y-maze performance was observed until the end of the third week following the last exposure to sarin. Thus, our findings confirm that both nonconvulsive symptomatic and clinically asymptomatic concentrations of sarin can cause relatively long-term memory impairments in sarin-poisoned rats when the rats are exposed to clinically asymptomatic sarin concentration repeatedly.
Keywords: Maze Learning; krysa rodu Rattus; bludiště - učení; Cholinesterase Inhibitors; Sarin; Male; Animals; Rats; mužské pohlaví; Administration, Inhalation; cholinesterasové inhibitory; aplikace inhalační; zvířata; sarin; Memory; paměť